Parents' perception of Denny Sumargo's Curhat Bang Podcast on Youtube, the episode of the case of the death of Kediri students - Khanifah, Nabila Ilmiyatul; Maghfira , Nur (Universitas Muhammadiyah Sidoarjo, 2024)
Youtube is an application that contains a collection of uploaded videos and has increased in popularity over the past five years, while Podcasts resemble radio programs because they contain audio content uploaded on YouTube. This study aims to determine the point of view of parents regarding the podcast content “Kediri Santri Death Case” on Curhat bang Denny Sumargo's Youtube channel which affects various views and mindsets circulating in the community, especially parents regarding the selection of educational institutions for children. This research uses a qualitative method by analyzing parents' perceptions through interview and observation data collection techniques. The conclusion of the research is that the parents' perception of the murder of students at the Tartilul Qur'an Islamic boarding school (PPTQ) Al Hanifiyyah has a positive response because the occurrence of the case depends on the supervision in the boarding school. Negative perceptions make their children traumatized and emotionally unstable in adolescence.